2003
DOI: 10.1159/000075097
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Brainstem Biopsy Is Indicated for the Diagnosis of a Vast Array of Brainstem Pathology

Abstract: Background/Aims: A meta-analysis of thirteen studies performing stereotactic biopsy of brainstem lesions is combined with our recent series of 12 patients with brainstem lesions comparing MRI findings to biopsy histopathology to determine whether these lesions could have been diagnosed radiographically. Methods: 12 consecutive stereotactic biopsies and literature analysis were performed to analyze clinical, radiographic and histopathologic data. Results: Stereotactic biopsy of lesions in the brainstem was in 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 12 publications
2
30
0
1
Order By: Relevance
“…Studies specifically on stereotactic biopsy of brainstem lesions give diagnostic rates comparable to more frequently biopsied supra tentorial lesions. [211172125262728] A recent meta analysis of 38 studies reported a diagnostic yield of 96.2% by weighted average proportions analysis. [16] In the present study, diagnostic yield of first stereotactic biopsy was noted to be 85.4%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies specifically on stereotactic biopsy of brainstem lesions give diagnostic rates comparable to more frequently biopsied supra tentorial lesions. [211172125262728] A recent meta analysis of 38 studies reported a diagnostic yield of 96.2% by weighted average proportions analysis. [16] In the present study, diagnostic yield of first stereotactic biopsy was noted to be 85.4%.…”
Section: Discussionmentioning
confidence: 99%
“…[20253038] This is also comparable to the complication rates reported for supratentorial biopsy. [227] The recent meta analysis of 1480 cases reported 7.8% overall morbidity, 1.7% permanent morbidity, and 0.9% mortality. [16]…”
Section: Discussionmentioning
confidence: 99%
“…In one study that demonstrated the utility of brainstem biopsy in patients with brainstem lesions, 18 of 46 patients had their diagnoses revised following brainstem biopsy as compared to relying on diagnostic value of conventional MRI alone [18]. In addition, image-guided stereotactic biopsy of brainstem lesions has been reported to be as safe as supratentorial biopsy [1921]. Only one of our patients who underwent brainstem biopsy developed new post-operative neurologic signs, and the mild dysarthria that ensued eventually resolved completely.…”
Section: Discussionmentioning
confidence: 99%
“…In children, some authors advocate a surgical biopsy to obtain tissue when the radiographic features are not consistent with a diffuse pontine glioma (35). Similarly, in adults, it is increasingly apparent that the heterogeneity of brainstem lesions complicates the ability to diagnose and prognosticate on the basis of imaging alone (14,22,37,39,40,44). Furthermore, limited insight into the cytoarchitecture, cellular composition, and origin of pediatric and adult brainstem gliomas means that tissue collection could accelerate the understanding of the disease (23,33,34).…”
mentioning
confidence: 99%